2014
DOI: 10.1093/pcp/pcu106
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Sugar, Light and Gibberellins in Expression of Rosa hybrida Vacuolar Invertase 1 Regulation

Abstract: Our previous findings showed that the expression of the Rosa hybrida vacuolar invertase 1 gene (RhVI1) was tightly correlated with the ability of buds to grow out and was under sugar, gibberellin and light control. Here, we aimed to provide an insight into the mechanistic basis of this regulation. In situ hybridization showed that RhVI1 expression was localized in epidermal cells of young leaves of bursting buds. We then isolated a 895 bp fragment of the promoter of RhVI1. In silico analysis identified putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 137 publications
2
16
0
Order By: Relevance
“…Gibberellins are a class of phytohormones that play a primary role in anthesis induction and sustainability ( Fos et al , 2000 ). Consistent with this, RhVI1 expression was found to be strictly dependent on gibberellins which were shown to enhance the expression of this invertase gene on its promotor ( Choubane et al , 2012 ; Rabot et al 2014 ). In this context, RhVI1 , modulated by gibberellins, behaves as an essential effector that acts as a bridge between the primary metabolism and the environmental stimuli ( Choubane et al 2012 ; Rabot et al 2014 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Gibberellins are a class of phytohormones that play a primary role in anthesis induction and sustainability ( Fos et al , 2000 ). Consistent with this, RhVI1 expression was found to be strictly dependent on gibberellins which were shown to enhance the expression of this invertase gene on its promotor ( Choubane et al , 2012 ; Rabot et al 2014 ). In this context, RhVI1 , modulated by gibberellins, behaves as an essential effector that acts as a bridge between the primary metabolism and the environmental stimuli ( Choubane et al 2012 ; Rabot et al 2014 ).…”
Section: Discussionsupporting
confidence: 71%
“…Plant invertases are mostly known as soluble proteins involved in several aspects of energetic metabolism ( Godt and Roitsch, 1997 ), with particular involvement in photosynthetic efficiency and regulation ( Büssis et al, 1997 ). In this study, we report the isolation and characterization of the membrane-anchored vacuolar invertase RhVI1 from petals of Rosa hybrida L. In previous work, it was shown that the expression of RhVI1 changes in buds under different illumination regimes and that RhVI1 codes for an enzyme with vacuolar localization on the basis of its sequence ( Girault et al , 2010 ; Rabot et al , 2014 ). This suggested a physiological significance of RhVI1 in processes such as anthesis where a high responsiveness to light and sugars is required ( Bartlett and Remphrey, 1998 ; Niinemets and Lukjanova, 2003 ; Kawamura and Takeda, 2004 ; Girault et al , 2008 ; Henry et al , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work had identified a set of genes contributing to rose bud outgrowth (Girault et al, 2010;Henry et al, 2011;Djennane et al, 2014;Barbier et al, 2015a;Supplemental Table S3), and for some of them, we gave evidence for photocontrol during this process: a positive light control for RhVI (Girault et al, 2010;Rabot et al, 2012Rabot et al, , 2014 and for RhSUC2 (Henry et al, 2011) genes, and a negative light control for RhNAD-SDH (Girault et al, 2010) as well as for the SL signaling RwMAX2 (Djennane et al, 2014) genes. Here, we further identified new homologous genes in rose that may be important in the control of bud outgrowth: SWEET10 involved in Suc transport (Chen et al, 2012), PCNA and CYCD3;1 involved in the cell cycle (Shimizu and Mori, 1998;de Jager et al, 2005;Moldovan et al, 2007), and EXP involved in cell wall expansion (Fleming et al, 1997;Dal Santo et al, 2011;Zenoni et al, 2011;Supplemental Table S1).…”
Section: Primer Design Of Genes Of Interestmentioning
confidence: 61%
“…Recently, sugars were shown to act as an initial trigger of bud release in pea (Mason et al, 2014) and as an early modulator of the key hormonal mechanisms controlling bud outgrowth in rose (Barbier et al, 2015a) under a favorable light environment. In rose, the transcription and enzymatic activity of vacuolar invertase (RhVI) as well as transcription of the Suc transporter gene RhSUC2 are under light control, and darkness leads to their repression concomitant with the inhibition of bud outgrowth (Girault et al, 2010;Henry et al, 2011;Rabot et al, 2012Rabot et al, , 2014. However, in vitro culture of excised rose buds in the presence of sugars does not rescue dark inhibition (Henry et al, 2011;Rabot et al, 2012), suggesting that sugars are not the initial target of the light signal that controls outgrowth.…”
mentioning
confidence: 99%
“…2 Our molecular analysis revealed that light acts in buds through transcriptional control of genes involved in major mechanisms of bud outgrowth (strigolactones-, auxin-, gibberellins-, sugar sink strength-, cells division and elongation-related genes). 1,[3][4][5][6][7][8] Recently, we demonstrated that cytokinins (CK) are early targets of the light signal perceived by buds. 1 Upon light perception by buds, CK synthesis in adjacent node and transport toward the buds is triggered within 3 hours where they control several bud outgrowth genes.…”
mentioning
confidence: 99%